Histotopography of receptors for lectins in some chick and human embryonic structures. - Lutay N.V.; Mashtalir M.A.; Brazaluk A.Z.; Tverdokhleb I.V. (Морфологія, 2007)
The distribution of the lectin-receptors for WGA, LCA, LAL, PSA, STA, PFA, SBA, PNA, VAA in the tissues of the chick embryos during 3-8 embryonic days and 10-weeks-old human fetus was investigated in this work. The selective binding with different structures of human fetus for all of lectins except for VAA was shown. The receptors for lectins were presented in the tissues of endodermal origin and in the some of the mesenchimal structures. The distinct density of the lectin-receptors distribution on the surface of the cells indicates that differentiation differs in the various cell populations. The amount of receptors for lectins was unchanged in the observed cell groups during chick embryogenesis. All of lectins except for HPL were bound by epithelial cells – surface ectoderm, ependimal layer of the neural tube, vascular endothelium, and mesothelium of the serose cavities. Apoptotic cells stained clearly in the heart, truncal and limb mesenchyme with LCA, RCA, and WGA. SNA stained the extracellular matrix containing a high level of the acid glycosaminoglycans.